Représentations gustatives de la femme dans le champ surréaliste grec - Diamanti Anagnostopoulou (Cahiers Balkaniques)
The surrealist man not only admires the woman, he wants to "eat" her; for him, the woman personifies the traits of a delicious fruit he wants to consume. Moreover, Lévi-Strauss points out the equivalence between the act of eating and that of copulating. The French surrealists, as well as Embirikos, sometimes Elytis, and occasionally Engonopoulos, liken the female body parts to beautiful fruit that erotic men want to taste. These food representations of women seem to contain both psychological and imaginary issues. For the surrealists, man desires to consume and possess the woman. Consumption can acquire at least symbolically a particular attribute of a condition, state or a desirable object, or to mark the effective possession. Consumption, possession, cannibalism, oral stage are closely related to representations of women in the surrealistic field. The woman becomes a consumable object but also a subject carrier of meaning, charged of imaginary that exercises individual and social, symbolic and real effects. These representations allow to "build" and to bring on the poetry scene both external reality and inner psychic reality.In the frame of this study, the aim is to examine the surrealistic representations of women and their symbolic and metaphorical dimensions. These dimensions will be analysed based on literary theory and psychoanalytic theory.